Faktor Penyebab Sibling Rivalry pada Anak Usia Dini di Kelurahan Tanah Pak Lambik Kota Padang Panjang - Zalita, Grabelia Dwi; Afrinaldi, Afrinaldi (ARZUSIN, 2023)
Sibling rivalry is a problem that often occurs in early childhood. Sibling rivalry will give rise to jealousy, conflict and disputes. The focus of the research is to determine the factors that cause sibling rivalry in early childhood in Tanah Pak Lambik Village, Padang Panjang City in children aged 2-6 years. This research is descriptive qualitative field research. This research uses observation and interview data collection techniques obtained from key informants and supporting informants in the field. The first factor is parental attitude, in the form of parents who only pay attention to one child and defend one child. Second, the positional order factor, it is known that parents assign more duties and roles to the first child or older child than to younger children. Third, the gender factor, with children of the same gender, namely girls and boys and boys and boys, there will be more frequent arguments and disputes between them. Fourth, the age difference factor is that some children are quite close to their siblings, giving rise to feelings of jealousy and older siblings who still cannot accept the presence of their younger siblings. Fifth, the number of siblings makes it possible for children not to want to have younger siblings because it will cause older children to fear that their parents' love will be divided. The six factors of parental discipline that provide democratic discipline still give rise to arguments. Seventh, the influence of outsiders is where children get more pleasure outside the home.